Kalendarium : geschiedenis van de Lage Landen in jaartallen - Jansen, H. P. H. (Hubertus Petrus Henricus), 1928-1985 (Utrecht : Spectrum, 1971)
Kalender
Keywords: Netherlands -- History -- Chronology; Belgium -- History -- Chronology